Analysis of Quality Defects in Plastic Seed Products Using Statistical Process Control (SPC) Method - Ubaidillah, Ubaidillah; Yuwono, Istantyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Plastic seed products are products made from recycled plastic materials such as raw materials for plastic bags and some screen printing plastics. UD. ABC is a company that produces PP (Polypropylene) plastic pellets. The existing problems include the discovery of instability in the production of plastic pellets which is in a negative direction for the company, namely there are product defects in plastic pellet products that exceed the standard defect tolerance limit of the company by 2%. Based on the Pareto diagram, it can show that the type of protrusion defect is 69.56% more dominant than the type of connecting defect, which is 30.44%. Based on the control chart based on the p-chart, it shows that some dates are outside the limits of the control chart, namely the sample lot number 3 (March) of 0.0352, 4 (April) 0.0273, 7 (July) 0, 0134, 8 (August) 0.271. The data that comes out of the control chart limits exceeds the upper control limit (BKA/UCL) of 0.02649 and the lower control limit (BKB/LCL) of 0.02395. So what must be done to repair the engine factor is to carry out periodic briefings on how the machine works starting from setting the temperature and changing the filter. Meanwhile, the human factors section, namely directing the replacement of machine filter workers with temperature operators so that workers do not get tired easily, conducting periodic supervision of each worker for the leader and providing guidance on knowledge about machine work systems, mixing raw materials and operating machine temperature controls regularly.